2011
DOI: 10.1371/journal.pone.0028831
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Expression Analysis Reveals Strategies of Burkholderia cenocepacia to Adapt to Cystic Fibrosis Patients' Airways and Antimicrobial Therapy

Abstract: Pulmonary colonization of cystic fibrosis (CF) patients with Burkholderia cenocepacia or other bacteria of the Burkholderia cepacia complex (Bcc) is associated with worse prognosis and increased risk of death. During colonization, the bacteria may evolve under the stressing selection pressures exerted in the CF lung, in particular, those resulting from challenges of the host immune defenses, antimicrobial therapy, nutrient availability and oxygen limitation. Understanding the adaptive mechanisms that promote s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 73 publications
(167 reference statements)
7
85
0
Order By: Relevance
“…[1][2][3] During long-term respiratory infections, CF opportunistic pathogens face a highly stressful and fluctuating environment within the patient's airways, in particular due to the host immune system, antimicrobial therapy, reduced availability of oxygen and other nutrients. [4][5][6][7][8] As a consequence, the initial infecting strain undergoes genetic changes resulting in parallel evolution within the lung with diversification of genotypes and phenotypes. 7,[9][10][11][12][13] The understanding of the mechanisms underlying microbial evolution within the CF host and its association with pathogenicity and persistence is crucial to deal with these chronic infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] During long-term respiratory infections, CF opportunistic pathogens face a highly stressful and fluctuating environment within the patient's airways, in particular due to the host immune system, antimicrobial therapy, reduced availability of oxygen and other nutrients. [4][5][6][7][8] As a consequence, the initial infecting strain undergoes genetic changes resulting in parallel evolution within the lung with diversification of genotypes and phenotypes. 7,[9][10][11][12][13] The understanding of the mechanisms underlying microbial evolution within the CF host and its association with pathogenicity and persistence is crucial to deal with these chronic infections.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate these mechanisms, our group has systematically compared the genome-wide expression patterns of 3 of the 11 Burkholderia cenocepacia sequential isolates examined in the present work, which were previously found to exhibit variation in relevant phenotypes in the context of bacterial pathogenesis. [4][5][6]12 These isolates were retrieved from one CF patient (patient J) chronically infected during 3.5 y until death with cepacia syndrome. 12 Late isolates (IST4113 and IST4134) were found to have a higher virulence potential compared to the first isolate (IST439) based on their higher ability to invade epithelial cells and to compromise epithelial monolayer integrity, 5 suggesting an increase of B. cenocepacia virulence throughout the course of long-term lung infection.…”
Section: Introductionmentioning
confidence: 99%
“…During CF lung infection, bacteria face an environment with a heterogeneous distribution of oxygen and nutrients, as well as high concentrations of antimicrobials. Several studies have shown that bacteria experience nutrient limitation during chronic lung infection (3)(4)(5)(6). Nitrogen is a major nutrient for cells, and nitrogen metabolism and its regulation have been studied in several bacterial species (7,8).…”
mentioning
confidence: 99%
“…However, in this study, we aimed to identify key virulence factors; most of these genes are likely common between the genomes of the highly problematic B. cenocepacia clinical strains and, thus, are detectable using this array. Furthermore, analogous data-mining approaches for strains other than J2315 were proven to be valid in several other studies (performed for the H111 [16] and IST439 [17] strains). A total of 36 arrays were performed to capture expression profiles from two sputum and two blood culture isolates that were each incubated in triplicate in (i) sputum, (ii) serum, and (iii) control medium.…”
Section: Resultsmentioning
confidence: 84%